2012
DOI: 10.1586/erc.12.130
|View full text |Cite
|
Sign up to set email alerts
|

Should African–Americans with elevated blood pressure be routinely screened for hypertensive heart disease?

Abstract: Keywords: diastolic dysfunction • hypertensive heart disease • left ventricular hypertrophy • left ventricular mass • systolic dysfunction • target-organ cardiac damage "Despite evidence showing a clear increase in the incidence of cardiovascular and cerebrovascular disease for African-Americans with hypertension, race is often overlooked as an independent risk factor. We contend that it should be considered as a stand-alone criterion for screening."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In conclusion, our data support the findings from previous studies that emphasize the need for intensive screening for early stages of hypertension-related cardiac damage to prevent symptomatic HHD in the elderly, where most cases occur [23][24][25][26][27][28], and suggest a need for national initiatives that will slow the progression of HHD in patients with hypertension and reduce the related risk of disability and premature death.…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, our data support the findings from previous studies that emphasize the need for intensive screening for early stages of hypertension-related cardiac damage to prevent symptomatic HHD in the elderly, where most cases occur [23][24][25][26][27][28], and suggest a need for national initiatives that will slow the progression of HHD in patients with hypertension and reduce the related risk of disability and premature death.…”
Section: Discussionsupporting
confidence: 89%
“…Although some perceive that screening of asymptomatic patients provides no long‐term benefit to morbidity, compelling arguments have been made for the utility of screening activities in communities that are predominately urban, African American and where limitations to healthcare access prompts heavy reliance on the emergency department (ED) for primary care . Increasing prevalence of the target condition is often tied to cost‐effectiveness of such approaches and, in the case of SHHD, has direct implications for intensification of antihypertensive therapy …”
mentioning
confidence: 99%
“…11,[32][33][34][35] Increasing prevalence of the target condition is often tied to cost-effectiveness of such approaches and, in the case of SHHD, has direct implications for intensification of antihypertensive therapy. 36 The development of preventable secondary complications of SHHD leads to substantial increases in morbidity, mortality, and health care costs. 37 Multiple studies have demonstrated that uncontrolled HTN is a significant risk factor for the progression of SHHD and the onset of chronic HF and other clinically overt conditions.…”
mentioning
confidence: 99%
“…This is consistent with previous studies that validated the Framingham CVD risk algorithm in African American populations 21,22 . However, to our knowledge this is the first time that the Framingham CVD risk score has been applied to a population at such high risk for hypertensive end organ damage 23 and our findings may guide future efforts aimed at risk stratification of ED patients with severely elevated BP 24 .…”
Section: Discussionmentioning
confidence: 79%